Development of Geogebra Assisted Electronic Student Worksheets (E-Worksheets) to Improve Student Independent Learning - Vera Dewi Susanti; Rika Wulandari (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
This study aims to produce teaching materials in the form of Electronic Student Worksheets (e-Worksheets) in the Geogebra Assisted Basic Mathematics Study course to increase student learning independence. The method used in this study is a model 4-D which consists of four phases, namely the define, design, development, and the disseminate. But in this study only up to the stage of development. Data was collected through the provision of validation questionnaires, student response questionnaires, and learning outcomes tests after using e-Worksheets. The results of the study show that: (1) The results of the validation for GeoGebra-assisted e-Worksheets are 3.08; learning outcomes test of 2.78 and learning independence questionnaire of 3.45 by experts (validators); (2) The results of the class trial were limited to the aspect of the student response questionnaire to the Geogebra-assisted e-Worksheets obtaining a score of 78.3% while the class trial results of 76.8% met the practical criteria. (3) And the results of the class trial were limited to the aspect of the student learning outcomes test, it can be seen that the percentage of student learning completeness is 80.21% while the results of the field class trial are 78.47% which indicates that the Geogebra-assisted e-Worksheets can be said to be effective.